2022
DOI: 10.1159/000525697
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Human Papillomavirus (HPV) and HPV Vaccination amongst the General Population in Germany: Lack of Awareness and Need for Action

Abstract: Introduction: The oncogenic human papillomaviruses (HPV) types 16 and 18 contribute to more than 73% cases of all HPV-related cancers and commonly affect the anogenital and head and neck region, with rapidly rising incidence rates of HPV-related oropharyngeal squamous cell carcinomas (OPSCC). HPV vaccination has the potential to decrease the burden of HPV-related disease but vaccination rates remain low in many countries. We investigated the level of awareness of HPV, and HPV-OPSCC in particular, in a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The reasons for the poor uptake in Germany are not well studied, but it is likely that there are several factors that contribute: (1) Awareness about HPV and HPV vaccination. In a population-based survey 64% of adults in Germany had heard about HPV, but only 45% of those knew that there are vaccines available to prevent HPV [ 19 ]. Hence, increasing awareness among the public seems to be one opportunity to improve coverage.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the poor uptake in Germany are not well studied, but it is likely that there are several factors that contribute: (1) Awareness about HPV and HPV vaccination. In a population-based survey 64% of adults in Germany had heard about HPV, but only 45% of those knew that there are vaccines available to prevent HPV [ 19 ]. Hence, increasing awareness among the public seems to be one opportunity to improve coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In the last couple of years and more during the COVID-19 pandemic, there was an obvious decrease in HPV vaccination rates along with a significant lack of awareness of HPV and HPV vaccination in many countries worldwide, such as: Germany [ 21 ], Austria [ 22 ], Italy [ 23 ], Saudi Arabia [ 24 ], United States [ 25 , 26 ], Japan [ 27 ], and Spain [ 28 ], as well as in Romania [ 1 , 12 , 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, since for HPV vaccination until 18 years of age parental consent is needed in Romania, an important factor that may raise the HPV vaccination rate in our country may be the parent. In Austria, for example, consent to receiving vaccines is regulated at the federal-state level, and, for example, in Tyrol, children aged 14 years are allowed to consent to receive vaccination [ 21 ]. In our study, we found out that women, female parents, are more likely to vaccinate their children against HPV p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with European countries, HPV vaccination rates in Germany are very low [ 5 ]. Furthermore, according to a study with a representative sample of the German population, awareness of HPV and HPV vaccination in the German population is significantly lacking [ 6 ].…”
Section: Introductionmentioning
confidence: 99%